دراسة ونمذجة مضخم ضوئي هجين لتحسين خصائصه وأدائه - عراج, فائق; صقور, عفيف; عيسى, هديل; عباس, نغم (Latakia University Journal -Engineering Sciences Series, 2019)
Hybrid Optical Amplifiers (HOA) are considered to be a promising and modern technology of great importance in high speed applications, which require a wide band of frequencies, and also in Wavelength Division Multiplexing (WDM) systems, since they enhance system performance without using costly technologies. This paper presents improving the performance of hybrid optical amplifier in terms of gain values, flatness, band width and noise figure. The properties of the hybrid optical amplifier, which is composed of two serially connected amplifiers: Raman Amplifier (RA) and Erbium Doped Fiber Amplifier (EDFA), are compared and analyzed. This research concentrates on the hybrid amplifier at both (C: 1530nm-1565nm) and (L: 1565nm-1625nm) bands for various cases of pumping. This amplifier is modeled using the MATLAB program, based on the propagation equations which represent the change in energy for distance and the rate equations that represent the change in the density of atoms in energy levels depending on time, and deriving analytical solutions for a two or three-level EDFA amplifier system in the absorption bands with wavelengths 980nm and 1480nm. The results are analyzed and optimal parameters are determined for both amplifiers in terms of input signal power, pump power, length of used fiber, etc. in each one. تعد المضخمات الضوئية الهجينة تقنية واعدة وحديثة ذات أهمية كبيرة في التطبيقات عالية السرعة والتي تتطلب عصابة عريضة من الترددات، وكذلك في نظم ارسال عدة رسائل دفعة واحدة بتقسيم اطوال الامواج الى مجموعات، كونها تعزز أداء النظام دون استخدام تقنيات مكلفة. تم في هذا البحث دراسة تحسين أداء المضخم الضوئي الهجين من حيث قيمة الربح وتسطحه، عرض العصابة الترددية ورقم الضجيج. وتمت مقارنة وتحليل خصائص المضخم الضوئي الهجين المكون من مضخمين موصولين على التتابع هما مضخم رامان Raman Amplifier) ((RA) ومضخم الليف المشاب بالاربيوم Erbium Doped Fiber Amplifier) :(EDFA. ركز هذا البحث على دراسة المضخم الهجين في كلا الحزمتين (C: 1530nm-1565nm), (L: 1565nm-1625nm) من اجل حالات الضخ المختلفة، حيث تمت نمذجة هذا المضخم بالاستعانة ببيئة MATLAB معتمدين على معادلات الانتشار التي تمثل تغير الاستطاعة بالنسبة للمسافة ومعادلات المعدل التي تمثل تغير كثافة الذرات في السويات الطاقية اعتماداً على الزمن، واشتقاق الحلول التحليلية لها من اجل نظام ثلاثي أو ثنائي المستوى لمضخم EDFA في حزم الامتصاص ذات الأطوال الموجية 980nm و1480nm، وتم تحليل النتائج واستنتاج البارامترات المثلى من اجل كلا المضخمين من حيث استطاعة إشارة الدخل, استطاعة المضخة, طول الليف المستخدم وغيرها في كل منهما.